Latin America and the Dragon: The Risks of an Economic-Commercial Relationship - Nacht, Pablo Alejandro (2013)
From a commodities perspective, this study deals with China’s great amount of raw material purchases in the region and Latin America’s commercial deficit, as well as the consolidation of neo-extractivism. From a manufacturing perspective, this article suggests the new international labor division does not only affect Mexico and Central America when competing with China and undergoing the delocalization of the maquiladora system, but it also takes a toll on the industry in countries like Brazil and Argentina. This study concludes that although some countries have seized the emerging power of China to secure a certain degree of autonomy before the United States and Europe, the costs for Latin America and the Caribbean are high, especially if the Beijing Consensus ensues.